2006
DOI: 10.1542/peds.2005-2580
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Premature Infants' Length of Stay and Improving Parents' Mental Health Outcomes With the Creating Opportunities for Parent Empowerment (COPE) Neonatal Intensive Care Unit Program: A Randomized, Controlled Trial

Abstract: A reproducible educational-behavioral intervention program for parents that commences early in the NICU can improve parent mental health outcomes, enhance parent-infant interaction, and reduce hospital length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
515
3
23

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(569 citation statements)
references
References 35 publications
15
515
3
23
Order By: Relevance
“…Melnyk et al (2006) in a study on the effects of an empowerment program on the mental health of mothers of premature infants, stated that implementation of the empowerment program was effective in the mood and emotional coping of mothers of premature infants (16). The similarities of these studies in terms of demographic characteristics and training content presented to mothers might account for the consistency in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Melnyk et al (2006) in a study on the effects of an empowerment program on the mental health of mothers of premature infants, stated that implementation of the empowerment program was effective in the mood and emotional coping of mothers of premature infants (16). The similarities of these studies in terms of demographic characteristics and training content presented to mothers might account for the consistency in the results.…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent randomized, controlled trial, the COPE program was associated with more positive interactions between parents and their infants, significantly less maternal stress in the NICU, and stronger parental beliefs regarding their role and the types of behaviors and characteristics to expect of their infants during hospitalization. 9 In addition, the infants of the parents who participated in this program had shorter lengths of stay in the NICU. Another trial reported that preterm infants who received developmentally supportive FCC exhibited less stress.…”
Section: Discussionmentioning
confidence: 99%
“…7 Evidence from clinical trials has attested to the benefits of FCC in terms of enhanced parent-infant interactions, better mental health for parents and improved outcomes for infants. [8][9][10] During the past two decades, providers have placed even greater focus on the value of the FCC approach for the care of preterm infants in the NICU, including the application of these principles to the transition home. [11][12][13][14][15][16][17] These efforts can be further advanced by learning about parents' experiences in the NICU and identifying potential areas of improvement.…”
Section: Introductionmentioning
confidence: 99%
“…36 Many authors and the AAP call for increased social support for these families. 5,[37][38][39][40] These interventions may be necessary to reap one of the few potential benefits of caring for a high-risk infant, that is, personal growth. Tedeschi and Calhoun 33 describe that individuals with strong social support systems are more likely to succeed at the cognitive processing essential for post-traumatic growth.…”
Section: Discussionmentioning
confidence: 99%